Silversmithing for jewelry makers a handbook of techniques and surface treatments - Bone, Elizabeth (Loveland Interweave Press, 2011)
"It will be love at first torch with this versatile guide--heating up both silver and your creative genius. Inside Silversmithing for Jewelry Makers, you'll find basic techniques and surface treatments, as well as advanced lessons on filigree, chasing, annealing, engraving, etching, and casting. Plus, youll get insightful profiles from contemporary crafted projects. This guide also offers a special bonus how-to-section for jewelry artists ready to showcase their work to customers. Silversmithing for Jewelry Makers is your go-to resource--no other creativity-driven, motivation-kicker will suffice."--From back cover.
Includes index.
Keywords: Jewelry making; Silverwork